Weapons grade : poems - Svoboda, Terese (University of Arkansas Press, 2009)
Terese Svoboda is the author of ten books of prose and poetry, most recently Black Glasses Like Clark Kent that won the Graywolf Nonfiction Prize. Her honors in poetry include the Iowa Poetry Prize and two prizes from the Poetry Society of America, the Lucille Medwick Award, and Cecil Hemley Award. She has also won an O. Henry Prize for the short story, the Bobst Prize for fiction, a Pushcart Prize for an essay, and a National Endowment for the Humanities fellowship in translation. Her opera WET premiered at Los Angeles Disney Hall in 2005. Svoboda lives in New York City.